Global citizenship, common wealth and uncommon citizenships - Shultz, Lynette; Pillay, Thashika (Comparative and international education (Sense Publishers), 2018)
"This set of essays critically analyze global citizenship by bringing together leading ideas about citizenship and the commons in this time that both needs and resists a global perspective on issues and relations. Education plays a significant role in how we come to address these issues and this volume will contribute to ensuring that equity, global citizenship, and the common wealth provide platforms from which we might engage in transformational, collective work. The authors address the global significance of debates and struggles about belonging and abjection, solidarity and rejection, identification and othering, as well as love and hate. Global citizenship, as a concept and a practice, is now being met with a dangerous call for insularism and a protracted ethno-nationalism based on global economic imperialism, movements for white supremacy and miscegenation, various forms of religious extremism, and identity politics, but which antithetically, also comes from the anti-globalization movement focused on building strong, sustainable communities. We see a taming of citizens that contributes to the taming of what we understand as the public sphere and the commons, the places of cultural, natural, and intellectual resources that are shared and not privately owned. The work of global citizenship education is distinguishable from the processes of a deadly globalization or destruction of the world that responds to the interlocking issues that make life on the planet precarious for human and non-humans everywhere (albeit an unequal precarity)"--